Early discharge of patients with pulmonary embolism in daily clinical practice: A prospective observational study comparing clinical gestalt and clinical rules. Issue 167 (July 2018) - Vanni, Simone; Becattini, Cecilia; Nazerian, Peiman; Bova, Carlo; Stefanone, Valerio Teodoro; Cimini, Ludovica Anna; Viviani, Gabriele; Caviglioli, Cosimo; Sanna, Michela; Pepe, Giuseppe; Grifoni, Stefano
Abstract: Objectives: To estimate the efficiency and safety of clinicians' gestalt in the identification of patients with pulmonary embolism (PE) candidates for early discharge and to compare the efficiency and safety of clinical gestalt with that of the Pulmonary Embolism Severity Index (PESI), the simplified PESI (sPESI) and the Hestia criteria (HC). Methods: Consecutive adult patients presenting to the emergency department of four Italian hospitals with confirmed diagnosis of PE were included. Data for PESI, sPESI and HC assessment were prospectively collected. Patients were managed according to the clinical gestalt of the attending physician, independent of the results of PESI, sPESI and HC. Efficiency was defined as the prevalence of candidates to early discharge. The primary safety measure was the incidence of a composite of venous thromboembolic recurrence, major haemorrhage or all-cause mortality within 30 days. Results: Out of 547 included patients, 178 (32.5%) were judged to be at low risk and discharged within 48 h from presentation. HC identified a higher proportion (41.7%) whereas both PESI (24.1%) and sPESI (18.3%) identified a lower proportion of candidates for early discharge when compared to clinical gestalt ( P  < 0.01 for all). The incidence of the safety outcome was 2.8% in early-discharged patients according to clinical gestalt and 2.3%, 3.0% and 2.6% in candidates to early discharge according to PESI, sPESI and HC, without differences between strategies. Conclusions: In our cohort, clinical gestalt identified one-third of PE patients for early discharge. Among different strategies HC showed the highest efficiency sharing similar safety with the other strategies. Highlights: Early discharge of low-risk patients with pulmonary embolism has been suggested, but scarce data were available in everyday clinical practice. We showed that in daily clinical practice, given the presence of a dedicated outpatient pathway, about one third of PE patients can be safely managed by early discharge. Three clinical rules were compared with clinical gestalt; Hestia Criteria showed the highest efficiency with non-inferior safety.